Hemiscorpius lepturus venom induces expression and production of interluckin-12 in human monocytes. (15th June 2015) - Hadaddezfuli, Reza; Khodadadi, Ali; Assarehzadegan, Mohammad-Ali; Pipelzadeh, Mohammad Hassan; Saadi, Samahir
Abstract: The objective of this study was to evaluate the capacity of the venom from Hemiscorpius lepturus to induce expression and production of interleukin-12 (IL-12) on isolated human monocytes. For this purpose, isolated human monocytes (250, 000–300, 000 cells/ml) were exposed to different concentrations of the venom (0.625, 1.25, 2.5, 5, 10 and 20 μg/ml) in 96-well plates for varying incubation periods (6, 12, and 24 h). The end point of assessment included LDH cytotoxicity assay, measurement of expression of IL-12, p40 mRNA by real-time PCR, and quantification of IL-12 release using sandwich ELISA technique. The results showed that this venom produced concentration- and time of incubation-dependent cytotoxicity. The level of enhancement of expression and production of IL-12 were found significantly higher with lowest concentration and after 6 h of incubation. The findings demonstrated that the venom from this scorpion contains active constituents which can direct the immune system to produce IL-12. Highlights: Venom of Hemiscorpius lepturus produced concentration-dependent cytotoxicity. Venom of H. lepturus induced time of incubation-dependent cytotoxicity. The venom from H. lepturus increases expression of IL-12 in human monocytes. The venom from H. lepturus can direct the immune system to produce IL-12.